Bangladesh : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses key findings of the Fourth Review Under the Poverty Reduction and Growth Facility (PRGF) for Bangladesh. Several quantitative and structural performance criteria have been missed for the fourth PRGF review. The nonobservance of these performance criteria largely reflects delays in securing the disbursement of external program assistance and difficulties in achieving the necessary internal consensus for advancing key structural reforms. In view of the remedial measures implemented by the authorities, IMF staff supports the requests for waiver of performance criteria.